2020
DOI: 10.1088/1361-6463/ab5f2f
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent exciton binding energy in semiconductor nanostructures

Abstract: In order to clarify the exciton binding energy (EBE) in semiconductor nanostructures, we investigate the size-dependent bond identities based on the atomic-bond-relaxation consideration. Taking into account the shell/core configuration of semiconductor nanostructures, we find that the changes in bond length and bond angle respectively decrease and increase as the dimensions of nanostructures diminish. Moreover, the EBE increases as the size decreases with a dependence, where D and p  are the size and sublinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…where t j is one-electron kinetic energy, the subscript j runs for all orbitals, and ∑ j n j t j = T s (6) is the total independent-particle kinetic energy for the Kohn-Sham auxiliary system. It is not the true electronic kinetic energy of the prototype system, and a part of E XC should account for their difference.…”
Section: Formal Derivationmentioning
confidence: 99%
See 1 more Smart Citation
“…where t j is one-electron kinetic energy, the subscript j runs for all orbitals, and ∑ j n j t j = T s (6) is the total independent-particle kinetic energy for the Kohn-Sham auxiliary system. It is not the true electronic kinetic energy of the prototype system, and a part of E XC should account for their difference.…”
Section: Formal Derivationmentioning
confidence: 99%
“…Optical absorption could generate electron-hole pairs, but they have electrostatic attraction in general. Therefore, the optical gap is usually smaller than the fundamental gap due to the finite exciton binding energy [6]. Sometimes the measured optical gap can be larger than the fundamental gap due to the optically forbidden transition [7], but that corresponds to special cases and will not be considered here.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the physical properties of excitons in perovskite materials are an important part of the study of their luminescence process. In addition, it has also been well reported that the size of the semiconductor material significantly affects the exciton binding energy of the material, thereby affecting the light-emitting performance of the material [44]. Bastard et al calculated in detail the influence of quantum well width on exciton binding energy [45], and Elward et al found through calculations that the exciton binding energy in CdSe quantum dots decreases as the material size increases [46].…”
Section: Resultsmentioning
confidence: 99%
“…[71] As an important part of many materials such as composite materials and heterojunction structures, interface plays a very important role in the performance regulation, so it has attracted attention of many scholars. [72][73][74][75] Specific to the field of crystalline-amorphous interface, the importance of the interface is mainly reflected in the mechanical properties of the structure, especially the plastic deformation ability. Wang et al [15] prepared the Cu/CuZr crystalline/amorphous multilayers and agree that the amorphous-crystal interfaces exhibit unique inelastic shear (slip) transfer characteristics, fundamentally different from those of grain boundaries.…”
Section: Plastic Deformation Mechanism In Amorphous Phasementioning
confidence: 99%